Interaction between calcitonin gene‐related peptide‐immunoreactive neurons and satellite cells via P2Y12R in the trigeminal ganglion is involved in neuropathic tongue pain in rats. (11th October 2017) - Sugawara, Shiori; Okada, Shinji; Katagiri, Ayano; Saito, Hiroto; Suzuki, Tatsuro; Komiya, Hiroki; Kanno, Kohei; Ohara, Kinuyo; Iinuma, Toshimitsu; Toyofuku, Akira; Iwata, Koichi
Abstract : The P2Y12 receptor expressed in satellite cells of the trigeminal ganglion is thought to contribute to neuropathic pain. The functional interaction between neurons and satellite cells via P2Y12 receptors and phosphorylated extracellular signal‐regulated kinase 1/2 (pERK1/2) underlying neuropathic pain in the tongue was evaluated in this study. Expression of P2Y12 receptor was enhanced in pERK1/2‐immunoreactive cells encircling trigeminal ganglion neurons after lingual nerve crush. The administration to lingual nerve crush rats of a selective P2Y12 receptor antagonist, MRS2395, attenuated tongue hypersensitivity to mechanical and heat stimulation and suppressed the increase in the relative numbers of calcitonin gene‐related peptide (CGRP)‐immunoreactive neurons and neurons encircled by pERK1/2‐immunoreactive cells. Administration of the P2Y1, 12, 13 receptor agonist, 2‐(methylthio)adenosine 5′‐diphosphate trisodium salt hydrate (2‐MeSADP), to naïve rats induced neuropathic pain in the tongue, as in lingual nerve crush rats. Co‐administration of 2‐MeSADP + MRS2395 to naïve rats did not result in hypersensitivity of the tongue. The relative number of CGRP‐immunoreactive neurons increased following this co‐administration, but to a lesser degree than observed in 2‐MeSADP‐administrated naïve rats, and the relative number of neurons encircled by pERK1/2‐immunoreactive cells did not change. These results suggest that the interaction between activated satellite cells and CGRP‐immunoreactive neurons via P2Y12 receptors contributes to neuropathic pain in the tongue associated with lingual nerve injury.